(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This paper examines the impact of social-emotional education on cultural dynamics from the perspective of Cultural Studies. An exhaustive theoretical review is carried out to analyze how social-emotional education can influence the construction and transformation of cultural identities. In addition, a mixed methodology is carried out that combines qualitative and quantitative analysis to evaluate the effects of social-emotional education programs in different cultural contexts. The results reveal that social-emotional education promotes empathy, intercultural respect and inclusion, thus contributing to a greater understanding and appreciation of cultural diversity. In conclusion, the importance of integrating social-emotional education into educational curricula as a key tool to foster peaceful coexistence and intercultural dialogue is highlighted.